Results of Mohs' Micrographic Surgery of Periocular Basal Cell Carcinoma: The Swedish Experience - Kalliopi Erripi; Daniel Paussen; Karin Svedberg (Medical Journals Sweden, 2024)
The Department of Ophthalmology, Sahlgrenska University Hospital, has until recently been the only eye clinic in the Nordic countries to perform Mohs' micrographic surgery of basal cell carcinoma. This has led to the practice of only the most complicated basal cell carcinomas being operated on with this technique. The purpose of this study was to present the results of these surgeries in patients with at least 5 years of follow-up. A retrospective study of all patients operated upon in 2010-2015 was performed. Data were gathered from their medical charts. Primary outcome was recurrence of basal cell carcinoma. One-hundred and sixty-seven patients were operated on. Mohs' micrographic surgery was used for tumours that were judged as highly aggressive on preoperative biopsy, had ill-defined borders, had recurred after previous surgery, or a combination of these factors. Nine recurrences (5.4% of all radical Mohs' micrographic surgeries) were diagnosed after a mean postoperative time of 37 months (4-84 months). Interestingly, all of these 9 recurrences after Mohs' micrographic surgery were in patients who had such surgery because of a recurrent basal cell carcinoma to start with. Good results can be achieved when operating on the most complicated periocular basal cell carcinomas with Mohs' micrographic surgery but special care has to be taken to ensure radical borders when operating on recurring basal cell carcinomas.